Studi Korelasi tentang Pemahaman Pentingnya Ibadah Shalat dan Pengamalannya - Rubino Rubino (Jurnal Pendidikan Madrasah, 2018)
This research aims to find out the correlation between the understanding of the importance of prayer worship and practice for students of SMK N 2 Wonosari Gunungkidul. This research using library research. The results showed that there was a relationship or a convincing correlation between the understanding of the importance of prayer and the practice of Worship for students grade 10 SMK N 2 Wonosari Gunungkidul training year 2017/2018. The results of the calculation of the value of the correlation coefficient between variables Moment Product Knowledge of the importance of prayer Worship (variable X) and practice (variable Y) for students of SMK N 2 Wonosari, Gunungkidul can note that a 5% level, r xy = 0.458 and r = 0.274. While the standard of 1%, r xy = 0.458 and r = 0.361, shows that the two are significant.